Board credit committee intangibles of banks in the Sub-Saharan Africa - Mohd ‘Atef Md Yusof, Murtala Aliyu Ibrahim, (Opción, 2019)
The purpose of this paper is to examine the association between Board Credit Committee Intangibles (BCC) and Credit Risk Management (CR) of the Sub-Saharan African (SSA) banks. The BCC Intangibles measured using the Sveiby’s (1997) Intangible Assets Monitor model are the committee independence (RIND), committee chair independence (CIND), committee size (RSIZ), committee financial expertise (RFIX), the frequency of meetings (RMEE) and diligence of the committee members (RDEL). The study adopted financial capital adequacy (FCA), profitability (PRO) and growth rate of GDP as control variables.